Tourism Vulnerability to Disaster: Impact of Epidemic, Natural Disaster, and Terrorism (Evidence from Indonesia) - Ahmad Rifai Sapta; Muhammad Hanri (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2023)
This study aims to explore the impact of multiple disasters, such as pandemics, natural disasters, and terrorism, on inbound tourists in Indonesia. Using a panel data approach, we studied the impact of these disasters by analyzing data regarding international tourist flow from 19 countries and nine ports of entry from 2008 to 2020. The results showed that different types of disasters affected inbound tourists differently in terms of magnitude and significance. In addition, some disasters had a longer-lasting impact, which can be seen from the significant negative impact in the year following the disaster. We also uncovered an impact that varied among tourist origin countries according to their responsiveness to the disaster. The findings imply that sustainable tourism development can not be achieved without understanding how disasters affect tourism.